Safe and Sound: Governance for Planning Public Space in a Security-by-Design Paradigm - Massari, Martina; Longo, Danila; Branchini, Sara (Urban science, 2025)
Security in public spaces has long been the subject of debate and extensive experimentation. With the exponential growth in risks (both expected and unexpected) that public spaces are exposed to, further exacerbated by the pandemic crisis, urban security management increasingly conflicts with the right to social interaction in space. To avoid creating overly controlled spaces that are unsuitable for generating sociality and spontaneous interactions, and which often reproduce discriminatory social dynamics, while at the same time ensuring users’ awareness of being in a safe environment, it is necessary for all three dimensions of public space security—policy, design, and governance—to converge. This study focuses on governance, exploring how security management shapes public life and how it can align with planning that supports vibrant, spontaneous interaction. Using a multi-method qualitative approach, including a critical literature review, EU policy analysis, and empirical research from the Horizon Europe SAFE CITIES project, the study introduces two tools: the Security and Vulnerability Assessment (SVA) framework and the Atlas for Safe Public Spaces Design. These were tested in pilot sites, including the Gorizia-Nova Gorica cross-border square. Results support a governance model integrating “security by design,” which aligns with Foucault’s view of governance as adaptable to uncertainty and flow. This mixed-method approach allowed for a comprehensive examination of the governance dynamics shaping urban security, ensuring that the study’s conclusions are grounded in theoretical insights and practical implementation, though necessarily limited in generalizability. By framing security as a process of negotiated governance rather than a set of technical constraints, the study offers a conceptual contribution to urban security discourse and practical guidance for planning secure, inclusive public spaces.